Phenolic compounds in coconut (Cocos nucifera L.) endosperm - Baldiviano, Perla F. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1999)
The phenolic compounds content of liquid and solid coconut endosperms at three stages of maturity were quantitatively determined by three methods. The three types of phenolic compounds, total phenol content, vanillin-positive or flavan-type phenolics and protein-precipitating polyphenols or condensed tannins decreased during the maturation of solid endosperm: total phenols from 4.01 to 1.00 mg catechin/g dry sample or catechin equivalents (CE), flavan-type phenolics from 0.40 to 0.06 CE, and protein-precipitating polyphenols from 2.64 to 0.64 mg tannic acid/g dry sample or tannic acid equivalents (TAE). The phenolic content values obtained at three stages of maturity of coconut liquid endosperm were similar and 20-60 times lower than those of the solid endosperm.